Analisa Pengaruh Panas Pengelasan Pada Pembuatan Foot Step Sepeda Motor - WAHYUDI, Joko, Patna Partono, ST, MT (2016)
Metallurgical research on motorcycle components can provide data on the physical and mechanical properties. From these data can then be used for better planning so that would be obtained more quality products. This study focused on the influence of welding heat to changes in microstructure and hardness in the manufacture of components foot step. This study uses a specimen of footstep component Yamaha brand motorcycles and local products. Tests conducted is a test chemical composition with ASTM E350-12, testing microstructure with ASTM standard E3, and Hardness testing with ASTM E18 -15. From the results of testing the chemical composition footstep Yamaha is known that the original product containing 98.74% Fe element and an element of C 0.178%, while the imitation product containing 98.79% Fe element and an element of C 0.169%. Carbon content greater than the original product imitation products. The content of other elements did not have much effect because it was too small. Both products are equally including low carbon steel. In the picture microstructure all contain grains of ferrite and perit, only ferrite grains more dominant than the granular perlite, foot step because the material is low carbon steel. The original product harder than the imitation products as the original product has a higher carbon content than the imitation product. Of the heat from the welding process flowing at the stem causing steel metal ferrite grains become larger. As a result, in the HAZ (heat affected zone) hardness being dropped.